Optimalisasi Kondisi Kerja di Bengkel Las Desa Pawidean Melalui Analisis Beban Kerja Mental dengan Metode NASA-TLX - Yohandika Tri Apriliyanto; C. Alba Pradhana; A. Farhan; C. Irawan; Beta Arya Ash. S (Politeknik Negeri Indramayu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in supporting economic growth in various countries, including Indonesia. One form of MSME that is developing in Indonesia is welding workshops which are classified as light manufacturing industries. This type of work environment has the potential to cause fatigue, stress, and decreased concentration, which can ultimately increase the risk of work accidents. This study aims to measure the level of mental workload of mechanics using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method, which assesses six main aspects: mental demands, physical demands, time demands, personal performance, effort, and frustration levels. The results of the study showed that operators with the highest mental workload obtained a NASA-TLX score of 88.667, while the lowest was 68.667. This shows that the average workshop operator experiences a high mental workload. The main factors causing this high workload include high time pressure, where the operator must complete the work in a limited time with a limited workforce of only 6 people. To reduce mental burden, workshops can take corrective measures such as providing supporting facilities, simplifying work systems, limiting last-minute orders, implementing re-inspections, and providing incentives for employees who work overtime to increase job satisfaction.